Evaluation of the Loop-Mediated Isothermal Amplification Assay (LAMP) Eazyplex® Pneumocystis jirovecii - Scharmann, Ulrike; Kirchhoff, Lisa; Buer, Jan; Schuler, Franziska; Serr, Annerose; Rößler, Susann; Held, Jürgen; Szumlanski, Tobias; Steinmann, Joerg; Rath, Peter Michael (Journal of Fungi, 2025)
A commercially available loop-mediated isothermal amplification assay (LAMP) for the detection of Pneumocystis jirovecii (P. jirovecii) has been evaluated for the diagnosis of Pneumocystis pneumonia (PcP) in critically ill patients. Altogether, 109 lower respiratory tract specimens from 95 patients with a positive P. jirovecii test in routine diagnostics were collected from five distinct university hospitals in Germany. All samples were tested with a qPCR and eazyplex® LAMP assay. qPCR was set as the gold standard and was evaluated beforehand with samples from 100 patients categorized to have proven, probable, and possible PcP according to the EORTC/MSGERC guidelines. The sensitivity, specificity, and positive and negative predictive value (PPV and NPV) of the LAMP were assessed. Sensitivity was 68%, specificity was 86%, and PPV and NPV were 99% and 16%, respectively. All patients with proven PcP were positive in the LAMP. There was a weak correlation between the time to positivity and the fungal load (squared Pearson correlation coefficient (r2) = 0.5653). A positive result in the LAMP indicates a PcP. Because of the low sensitivity, negative results do not rule out an infection and should be clarified with further molecular methods. The LAMP should be used in patients in whom a PcP is expected, not for screening only.
CRIS-Team Scopus Importer:2025-05-09
Keywords: fungal infection; LAMP; molecular diagnostic; Pneumocystis jirovecii; pulmonary infection; qPCR